Marine Debris Identification and Ecotourism Management on Hoga Island Kaledupa District Wakatobi Regency - Haerudin La Turi; Muhammad Yasser; Widya Kusumaningrum; Hamdhani Hamdhani; Paulus Taru; Omega Raya Simarangkir (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
This study aims to identify the types and management of ecotourism on Hoga Island, Kaledupa District, Wakatobi Regency. This research was conducted by observing three transects, divided into transect 1 (Hoga island gate area), transect 2 (lodging area on Hoga island) and transect 3 (tourist recreation center beach area) with shoreline survey methodology method with transect size of 5 m × 5 m. The results showed that the waste found on Hoga island belongs to the category of macro-type waste with a total of 64 and an abundance of 2.56 particles / m2 dominated by plastic by 75%. The most marine debris is found in transect 3 with an amount of 37 and a weight of 1,323 g. Meanwhile, transect 1 found 15 waste 777 g in weight and transect 2 as much as 10 waste weighing 268 g. The management of ecotourism on Hoga Island is regulated by the local government without involving the community and local village governments. The socioeconomic interests of the community are not accommodated in local government policies, so that individually local communities participate in the field of services in developing ecotourism and meeting needs. Some of the offers offered are transportation services, management of tour guide homestays, administrative managers, marketing of local products and cultural creations.